ANALISIS KOMPOSISI GAS BUANG AKIBAT PERUBAHAN MAIN JET NOZZLE PADA SISTEM KARBURATOR MESIN - Bernadi Ksatria Putra; Abrar Riza; Asrul Aziz (Jurnal Ilmiah Teknik Mesin POROS, 2017)
Abstract: Fuel entering through the main jet nozzle, affects engine performance and the composition of the exhaust gas is produced. Research the composition of the exhaust gases in machines otto one cylinder done with experimental method. The purpose of this study was to obtain the characteristics of the engine with exhaust gas analysis method. This research done with varying size main jet nozzle and varying the engine rotation every 400 rpm. Data processing the results of testing includes a comparison of the composition of the exhaust gases is HC, CO2, CO, O2, AFR, and the temperature of the exhaust gases. Then calculate the enthalpy of combustion for each main jet nozzle. The composition of the exhaust gases are best obtained from the main jet nozzle GX 160 which has the highest CO2 value of 20%, with the lowest CO value of 1.26% and the largest combustion enthalpy value with the value of 264.769 kJ. From the analysis can be known that the burning of the main jet nozzle GX 160 approaching the stoichiometric combustion.